Colonic transit in subjects with spinal cord injuries - Freedman, Patricia Noel (Division of Nuclear Medicine, 2017)
The rehabilitation of patients with spinal cord injuries (SCI) is long and difficult. Not only do they lose mobility but they also have changes in bowel continence caused by loss of voluntary motor and sensory function and damage to the visceral nerve supply. The maintenance and management of bowel function causes major morbidity for subjects with SCI. The effect of SCI on colonic function is poorly understood and little studied. Aim: This study sought to establish a method of studying regional colonic transit and to investigate whether the level of SCI influences colonic transit. Patients and Methods Sixteen subjects (8 paraplegics and 8 tetraplegics) with spinal cord injury, at least one year previously were recruited. The tetraplegics group had spinal cord injuries above T1 and the paraplegic group had injuries below T1 . They were given a pancake labelled with 10-18 Mbq of ln-111 Amberlite resin to eat. Anterior and posterior images were acquired for 400 seconds each, using a 40 cm field of view gamma camera, once on the first day and then 3 times a day for the next 4 days. The subjects were asked to report every time they had a bowel evacuation. No laxatives or enemas were permitted during the study. Subjects were permitted to eat and drink normally after the first images (3 hours) were acquired. Seven regions of interest (ROI) outlining, 1) ascending colon, 2) hepatic flexure, 3) transverse colon, 4) splenic flexure, 5) descending colon, 6) rectosigmoid and 7) total abdominal activity, were drawn on each set of anterior and posterior images. The counts were decay corrected. The decay corrected counts were used to calculate the geometric mean (GM), for each region, at each time point. The GM was used to calculate the percentage of the total abdominal activity in each region, at each time point. Colonic transit was assessed in 4 ways. Firstly, 3 independent Nuclear Medicine Physicians visually assessed transit on hard copies of the images and classified subjects into 5 categories of colonic transit (rapid transit, intermediate transit, generalised delay, right-sided delay or left-sided delay). Secondly, parametric images were constructed from the percentage activity in each region at each time point. Thirdly, the arrival and clearance times of the activity in the right and left colon were plotted as time-activity curves. Finally, the geometric centre of the distribution of the activity was calculated and plotted on a graph versus time. The parametric images, time activity curves of the right and left sides of the colon and the geometric centre for each subject were classified into the same categories as the visual assessment. All statistics were assumed to be non-parametric. Results: The results of the four methods of assessing colonic transit were compared and the majority categorisation was accepted as the final diagnosis. The best agreement occurred between the parametric images and the arrival and clearance times of the activity in the right and left colons. No single method was consistently correct. Amongst the paraplegic subjects, two had generalised delay, four had rightsided delay, and two left-sided delay. In the tetraplegic subjects, two had intermediate transit, 1 generalised delay, and 5 left-sided delay. Conclusion A combination of at least two methods of determining colonic is necessary. The level of spinal cord injury effects colonic transit. Injuries below T7 /T8 result in right-sided delay. Injuries above this most commonly result in left-sided delay. Occasionally injuries above T7/8 can result in intermediate transit or generalised delay. Paraplegics are more likely to have right-sided delay (p =0.04), whereas tetraplegics are more likely to have left-sided delay.